Dental and Periodontal Status of 5 and 12 year old Children in Jakarta and it's Satellite Cities - Melissa Adiatman; Afida Luthfi Yuvana; Avina Anin Nasia; Anton Rahardjo; Diah Ayu Maharani; Shinan Zhang (Faculty of Dentistry, Universitas Indonesia, 2016)
Jakarta is the capital city of Indonesia which is surrounded by its satellite cities Bogor, Depok, Tangerang, Bekasi, which can be shortened by Jabodetabek. Objective: The study aims to describe oral health among 5 and 12 years-old children in Jabodetabek. Methods: This cross-sectional oral-health survey was conducted from 2014 with ethics approval. Sample of 5-year-old and 12-year-old Indonesian children living in Jabodetabek were selected using cluster sampling method. One trained examiner performed the clinical examination. Caries experience was measured using DMFT index, severity of decayed teeth was assessed using PUFA index, gingival status and oral hygiene were measured by Loe and Sillness modified index. Results: A total of 390 5-year-old and 458 12-year-old children with balanced proportion between girls and boys participated the survey. The prevalence of caries experience among the 5-year-old children and 12-year-old children were 90% and 84% respectively. The mean DMFT and DT scores among the 5-year-old children and 12-year-old children were 7.5±5.5 and 6.8±4.8; 3.2±2.2 and 2.9±2.1 respectively. Pulp involvement were apparent in 45% and 23% of caries in 5 and 12-year-old children respectively. Most children, 45% 5-year-old children and 92% 12-year-old children had substantial amount of plaque. Moreover, 68% 12-year-old children had gingivitis. Conclusion: Dental caries were prevalent among 5 and 12-year-old Indonesian children in Jakarta its satellite cities. The oral health condition of most of the children were poor. DOI: 10.14693/jdi.v23i1.982